Executive Committee Minutes 2019-02-07 - Academic Senate:::::::::
Agenda Approved. Minutes of 1/25/19 – Approved. Chair Report. President Report. Provost Report. Vice Chair Report. VP of Administration and Finance Report. VP for Student Affairs Report. Associated Students Report. Reassigned Time for Faculty Governance 2019-2020 – Approved to forward to the Provost. Resolution re: President's Climate Leadership Commitment – approved for the Senate agenda in correct format. Instructor Drops – policy and procedure creation referred to FSAC. APARC Report. EPC Report. FSAC Report. SAC Report. CFA Report. SEC Rep to Ex Com Report. Senate agenda – approved. Request for academic technology and accessibility of classroom materials update to Senate.